Balloon Pulmonary Angioplasty for Takayasu Arteritis and Peripheral Pulmonary Artery Stenosis Mimicking Chronic Thromboembolic Pulmonary Hypertension - Shigefumi Fukui; Yuko Shirota; Takao Nakano; Tsukasa Sato; Kaoru Hasegawa; Hisashi Kikuta; Takeyoshi Kameyama; Koji Kumagai; Tatsuya Komaru (Life, 2022)
Balloon pulmonary angioplasty (BPA) has been reported to be effective and safe to an acceptable level in patients with distal-type, inoperable chronic thromboembolic pulmonary hypertension (CTEPH), resulting in improved long-term survival. However, evidenced treatment options and strategy including medical therapy of antithrombotic therapy, glucocorticoids, immunosuppressants, and pulmonary hypertension (PH)-specific therapies are scarce in patients with significant PH and right heart failure associated with Takayasu arteritis and peripheral pulmonary artery stenosis, both of which mimic CTEPH. Moreover, there has been still concern on safety and lack of established methodology in performing BPA for these conditions. In this report, we would like to review recent publications including several case reports and discuss the efficacy, safety, and suitable methods of BPA in this population.